2020
DOI: 10.7163/gpol.0171
|View full text |Cite
|
Sign up to set email alerts
|

The impact of social structure and physical characteristics on housing estate renovation in postsocialist cities: Cases of Vilnius and Budapest

Abstract: The article aims to analyse the renovation of housing estates in postsocialist cities. Two cities with different share of housing estates and public support system, Vilnius and Budapest are in the focus of the analysis. The renovation of housing estates is a new process in both of them; it started only in the 2000s and its outcome is far from spectacular. The most important and most common type of renovation activities is the insulation of blocks of flats because it significantly decreases the utility costs. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…However, the most important improvements must be made in common areas with common staircases, door sizes, and elevators in blockhouses. Studies have shown the significance of the residents' social status and the availability of state support, as exemplified in a recent analysis of housing renovation in Budapest and Vilnius (Szabó & Burneika, 2020). The reality in Riga is that renovated flats become affordable only for the economically wealthy minority.…”
Section: Incremental Renovation and New Apartmentsmentioning
confidence: 99%
“…However, the most important improvements must be made in common areas with common staircases, door sizes, and elevators in blockhouses. Studies have shown the significance of the residents' social status and the availability of state support, as exemplified in a recent analysis of housing renovation in Budapest and Vilnius (Szabó & Burneika, 2020). The reality in Riga is that renovated flats become affordable only for the economically wealthy minority.…”
Section: Incremental Renovation and New Apartmentsmentioning
confidence: 99%
“…They were mainly financed from EUsupport for refurbishment. Their results were spectacular in some LHEs (Kuusk & Kurniski, 2019;Szabó & Burneika, 2020), especially in the ones where the majority of buildings were renovated (Kovács & Herpai, 2011). However, the LHE renovation projects were not likely to result in social upgrading, population change or gentrification.…”
Section: Development Of Housing Estatesmentioning
confidence: 99%